Quality of human-animal interactions during beef cattle auctions in Panama - Cedeño, Joseph Kaled Grajales [UNESP]; Paranhos da Costa, Mateus J.R. [UNESP] (Elsevier, 2024)
This study aimed to determine the quality of human-animal interactions during cattle auctions in Panama and to assess the relationship between cattle reactivity, value paid, and time spent on commercialization. Data were recorded by watching video records of 4531 individual cattle sold in the main Panamanian auctions. Cattle reactivity was assessed by one previously trained observer when the animals entered the box where they were exposed for sale, assigning one of three scores: 1 = calm, 2 = reactive, and 3 = very reactive. Human-animal interactions were assessed using a binary score to assess the occurrence of hitting (1) or not (0) during commercialization. When cattle were hit to stimulate movement, their reactivity was assessed again to determine whether hitting altered their behavior. The value paid (USD/kg of live weight), and the time spent on commercialization (s) of each animal were also recorded in a subsample of 704 animals. Cattle reactivity, genetic group, animal category, auction location and phase of commercialization influenced the occurrence of hits (p<0.05). Hitting altered cattle reactivity (p<0.001); 95 % of the animals scored calm when they entered the auction box, dropped to 85 % after being hit. There was a significant effect of the reactivity score (p<0.05), genetic group (p=0.01), location (p<0.001) and auction phase (p=0.002) on the number of hits received by the cattle when inside the auction box. The median value paid for very reactive cattle tended to be higher than for calm cattle (1.85 vs 1.82 USD/kg; respectively; p=0.06). There were no differences in the time spent on commercialization according to cattle reactivity (p>0.05). In conclusion, cattle reactivity, and auction phase, in addition to other factors such as genetic group, animal category, and auction location, affected the frequency of negative human-animal interactions during commercialization. Cattle reactivity tended to affect the price paid per head of cattle but not the time spent in marketing.
Keywords: Animal welfare; Behavior; Cattle commercialization; Temperament